A new species of Laelaspis Berlese (Acari: Mesostigmata: Laelapidae) from Iran, with a revised generic concept and notes on significant morphological attributes in the genus - Kazemi, Shahrooz (Zootaxa, 2015)
A short diagnosis and a more detailed diagnosis of the genus Laelaspis are presented. Until now, a total of 40 described species belong to the genus, including a new species described here, and excluding the four following species previously described as Laelaspis or Hypoaspis (Laelaspis): L. badrii Nasr & Nawar [considered as Cosmolaelaps badrii comb. nov.], L. zuluensis Trägårdh, Hypoaspis (L.) lawrencei Van Aswegen & Loots, and Hypoaspis (L.) latodentis Karg. In addition, L. morazae sp. nov., is described on the basis of adult female and male specimens associated with Lepisiota semenovi (Ruzsky) (Formicidae) in Mashad County, northeastern Iran, and in the nest of an unknown ant in Shahreza County, central Iran. Laelaspis persicus is redescribed based on the holotype, paratype and additional specimens collected in north, southeastern and southwestern Iran.